COMPARATIVE ANALYSIS OF SOME TIGRINYA PROVERBS - Busau, Filip (Proverbium - Yearbook, 2020)
The present article largely draws upon the author’s thesis dealing with the topics of birth and death in Tigrinya proverbs, submitted at the Free University of Berlin, Germany. The paper investigates -parallels of some of these proverbs to those from other African as well as Mid- East-ern, European, and Asian language cultures. The relevance of the analysis lies in the fact that, although being the third largest modern Semitic language, Tigrinya remains not sufficiently studied, with many gaps in the academic research of this language, not to mention its proverbial heritage. Although the notion that Tigrinya proverbs have equivalents in other languages might suggest itself, hardly any documented evidence of it has been presented up to the present day. The following analysis thus takes a step toward the comparative study of Tigrinya proverbs by offering an annotated overview of selected proverbs and sayings with their correspondences in other languages.